A Severe Case of Overlap of Morphea and Eosinophilic Fasciitis after Burn Injuries - Hania Sami; Faria Sami; Shahzad Ahmed Sami; Abdulqadir J. Nashwan (Case Reports in Rheumatology)
Background. Generalized morphea is a rare fibrosing skin illness that progresses from erythematous, violet-colored skin patches to sclerotic plaques. Another uncommon immune-mediated connective tissue disease called eosinophilic fasciitis (EF) evolves to cause sclerosis and woody skin induration. The coexistence of the two is extremely rare and has a poorer prognosis. Our case report is one of the first to report burn injuries as a trigger factor for EF and generalized morphea overlap. Case Presentation. A 36-year-old man presented with acute onset of rapidly progressing skin thickening, tender edema, and skin contractures involving all extremities, shortly after enduring burn injuries from a gasoline explosion. Workup was remarkable for peripheral eosinophilia, hypergammaglobulinemia, and elevated C-reactive protein. Skin biopsy demonstrated sclerodermoid changes and sclerotic thickening of subcutaneous fibrous septa associated with stromal mucin, dermal perivascular, diffuse lymphoplasmacytic infiltrate with eosinophils, decreased CD34 expression, and increased factor XIIIa. He was subsequently diagnosed with an overlap of generalized morphea and eosinophilic fasciitis. The patient had only limited improvement with steroids, methotrexate, mycophenolate mofetil, and intralesional triamcinolone acetonide injections. Conclusion. Generalized morphea with concomitant EF indicates some degree of therapeutic resistance and poor prognosis with a low quality of life. Burn injuries can be a trigger factor for this overlap syndrome. Prompt identification of at-risk individuals and initiating aggressive management are necessary.